TLR expression profiles are a function of disease status in rheumatoid arthritis and experimental arthritis - Clanchy Felix I L (JOURNAL OF AUTOIMMUNITY, 2021)
The role of the innate immune system has been established in the initiation and perpetuation of inflammatory disease, but less attention has been paid to its role in the resolution of inflammation and return to homeostasis. Toll-like receptor (TLR) expression profiles were analysed in tissues with differing disease status in rheumatoid arthritis (RA), ankylosing spondylitis (AS), and in experimental arthritis. TLR gene expression was measured in whole blood and monocytes, before and after TNF blockade. In RA and osteoarthritis synovia, the expression of TLRs was quantified by standard curve qPCR. In addition, four distinct stages of disease were defined and validated in collagen-induced arthritis (CIA), the gold standard animal model for RA - pre-onset, early disease, late disease and immunised mice that were resistant to the development of disease. TLR expression was measured in spleens, lymph nodes, blood cells, liver and the paws (inflamed and unaffected). In RA whole blood, the expression of TLR1, 4 and 6 was significantly reduced by TNF blockade but the differences in TLR expression profiles between responders and non-responders were less pronounced than the differences between RA and AS patients. In RA non-responders, monocytes had greater TLR2 expression prior to therapy compared to responders. The expression of TLR1, 2, 4 and 8 was higher in RA synovium compared to control OA synovium. Circulating cytokine levels in CIA resistant mice were similar to naïve mice, but anti-collagen antibodies were similar to arthritic mice. Distinct profiles of inflammatory gene expression were mapped in paws and organs with differing disease status. TLR expression in arthritic paws tended to be similar in early and late disease, with TLR1 and 2 moderately higher in late disease. TLR expression in unaffected paws varied according to gene and disease status but was generally lower in resistant paws. Disease status-specific profiles of TLR expression were observed in spleens, lymph nodes, blood cells and the liver. Notably, TLR2 expression rose then fell in the transition from naïve to pre-onset to early arthritis. TLR gene expression profiles are strongly associated with disease status. In particular, increased expression in the blood precedes clinical manifestation.